Novel Techniques to Make Innumerable, Expectedly Safe, and Oily Systems to Make Intramuscular Injections (Solutions) of Poorly Oil Soluble Drugs Using Mixed Solvency Concept - Prajapati, Dharmendra (Asian Journal of Pharmaceutics (AJP), 2023)
A large number of blends of oily solutions containing oil soluble safe additives can be developed. The primary goal of the present study is to investigate the idea of mixed solvency concept. Pharmaceutical manufacturers can then use these blends to develop oily solutions for intramuscular injections that contain drugs that are poorly oil soluble. The main objective of this research is to provide oily intramuscular injection manufacturers some creative ideas. Utilizing the solubilizing properties of safe solubilizers, the solubility of poorly oil soluble drugs can be increased. After toxicological studies, it is anticipated that these injection formulations will be safe and such formulations can be marketed by the pharmaceutical manufacturers. According to the mixed solvency concept, every substance on earth has the ability to dissolve a solute in a solvent system. Hence, a concentrated oily solution containing a variety of oil soluble excipients might work well as a solvent for drugs that are poorly oil soluble. Such a concentrated solution might demonstrate the additive or synergistic solubilizing effects of the solubilizers present in solution for a specific solute.